The Effect of Eight Weeks of Selected Corrective Exercises on the Improvement of Musculoskeletal Disorders in Workers of A food Production Factory - hadi khalaji; ali yalfani; farzaneh gandomi (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction:Musculoskeletal disorders are one of the common causes of occupational injuries and disabilities in the developing countries. Such injuries are among the 10 injuries that lead to absenteeism. The purpose of this study was to investigate the effect of eight weeks of the selected corrective exercises on improving the musculoskeletal disorders and work satisfaction among workers of a food factory in Hamadan City of Iran. Method:In this quasi-experimental descriptive-analytical study, the statistical population included 180 people, of whom 32 participants were selected and assigned to the experimental (n=16) and control (n=16) groups. The Nordic questionnaire was administered to identify the participants' exposure to disorders. The VAS index was used to determine the severity of pain and the Minnesota questionnaire was applied to obtain work satisfaction. Frequency was used to determine the prevalence of musculoskeletal disorders. In order to determine the effect of selected exercises on pain and work satisfaction, independent and dependent t-test were applied. Results:The findings showed that most prevalent musculoskeletal disorders were in lumbar (58.25%), knee(47.57%), wrist (32.03%) and neck(31.03%), which require corrective and ergonomic tervetions. In addition, the results of paired t-test indicated that after 8 weeks of selected corrective exercises, the level of pain decreased significantly in lumbar (P=0.001) and knee (P=0.001) areas. In addition, work satisfaction increased significantly after this period (P=0.0001). Conclusion:The prevalence of musculoskeletal disorders in food factory workers was in the lumbar, knee, wrist, and neck areas, which require corrected and ergonomic interventions. The selected corrective exercises had positive effects on reducing the pain caused by musculoskeletal disorders and increasing the workers' job satisfaction.